Two patients with spontaneous transomental hernia treated with laparoscopic surgery: a review. Issue 4 (6th April 2018) - Inukai, Koichi; Takashima, Nobuhiro; Miyai, Hirotaka; Yamamoto, Minoru; Kobayashi, Kenji; Tanaka, Moritsugu; Hayakawa, Tetsushi
Abstract: Here, we report two patients with transomental hernia who were successfully treated with laparoscopic surgery. The first patient was a 58-year-old female who presented to our hospital with abdominal pain and vomiting; she had no history of abdominal surgery. Enhanced computed tomography revealed strangulation ileus due to an internal hernia. The second patient was a 36-year-old male who presented to our hospital with abdominal pain and no history of abdominal surgery. Enhanced computed tomography indicated transomental hernia. Emergency laparoscopic surgery in both patients revealed incarcerated bowel loops through defects in the greater omentum. The bowel segments were laparoscopically released, and the patients were uneventfully discharged on postoperative Days 4 and 8. Laparoscopic surgery is useful for the diagnosis and treatment of small bowel obstruction due to transomental hernia through the greater omentum.